Violência e mulheres em quadrinhos indígenas: estórias que resistem - Rodrigues, Noele Natália Miranda (2020)
This thesis aims to analyse the graphic novel Will I See? (2016) , written by two Indigenous Canadian writers, i skwé e David Alexander Robertson, from a critical theoretical perspective i nterested i n denouncing violent actions historically exerted against Indigenous women. Therefore, our goal i s to analyze how the theme of missing and murdered Indigenous women i s portrayed i n the graphic novel selected for our study; We discuss the way the publishing of comic books produced by Indigenous authors have been relevant for the discussion of such a subject i n contemporary Canada. Departing from the reading of theoretical and critical references on the subject, our purpose i s to reflect on this genre ( graphic novel ), discussing i ts characteristics, which have often been used by Indigenous people to create their l iterary representations. We also discuss violence experienced by First Nations, especially by their women l iving i n Contemporary Canada, taking i nto consideration studies questioning sexism and racism, mainly the one directed against native people. In this sense, we take studies by Joyce Green (2007), Allison Hargreaves (2017) and Paula Gunn Allen (1992) to discuss violence attached to Indigenous women. As a support for our reading of the l iterary production we are analyzing, we will take studies by Will Eisner (2008) and Gérard Genette (2009) into account, among others. Finally, our aim along this research was to collaborate with the questioning, from the perspective of post- or decolonial views, of the power relations established i n contemporary Canadian society, which keep being marked by a very selective type of violence, based on racial and gender criteria.